Colorectal cancer with a germline variant inherited paternally: a case report - Kyoung Min Kim; Min Ro Lee; Ae Ri Ahn; Myoung Ja Chung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
BRCA genes have well-known associations with breast and ovarian cancers. However, variations in the BRCA gene, especially germline variations, have also been reported in colorectal cancer (CRC). We present the case of a rectal cancer with a germline BRCA1 variation inherited from the paternal side. A 39-year-old male was admitted with rectal cancer. The patient underwent surgical resection and the pathologic diagnosis was adenocarcinoma. Next-generation sequencing was performed and a BRCA1 variant was detected. Reviewing the public database and considering the young age of the patient, the variant was suggested to be germline. The patient's father had had prostate cancer and next-generation sequencing testing revealed an identical BRCA1 variant. In the BRCA cancer group, there is relatively little attention paid to male cancers. The accumulation of male CRC cases linked to BRCA variations may help clarify the potential pathological relationship between the two.